KEAMANAN MANUSIA DAN EKOLOGI POLITIK DALAM PERTAMBANGAN KOBALT DI REPUBLIK DEMOKRATIK KONGO - Karimah, Hikmatul; Fadza , Muhammad Rafly Farezki; Indana, Naswa Syifa (Indonesian Journal of International Relations, 2025)
This study analyzes human security and political ecology issues in cobalt mining practices in the Democratic Republic of the Congo (DRC), a central hub in the global green energy supply chain. Employing a qualitative case study approach with content analysis, this research utilizes the UNDP's Human Security concept and Paul Robbins' Political Ecology framework as its theoretical lens. Findings reveal that mine workers, including women and children, operate under inhumane conditions without adequate legal protection. Such exploitation reflects the unequal power relations between global actors and local communities within the mineral supply chain. This study concludes that energy sustainability cannot be separated from principles of social and ecological justice, advocating for more ethical and accountable global mineral supply chain governance